The Mainspring and Recruiting Mechanism of the Egyptian Muslim Brotherhood under Authoritarian Regimes (JOURNAL OF SOCIAL SCIENCE RESEARCH, 2015)
To understand the Egyptian Muslim Brotherhood's mobilization phenomenon, the readers should look at different angles. Those angles are divided into two categories: the first category is based on macro-analysis, while the second is based on micro-analysis. The Macro-analysis is defined by the historical explanations based on the political or sociological explanations. The microanalysis in this paper presents the different mechanisms pursued by the experienced members of  the Egyptian Muslim Brotherhood. those stages are well studied and evaluated by the Organization